Multimorbidity Among Persons Living with Human Immunodeficiency Virus in the United States. (15th November 2017) - Wong, Cherise; Gange, Stephen J; Moore, Richard D; Justice, Amy C; Buchacz, Kate; Abraham, Alison G; Rebeiro, Peter F; Koethe, John R; Martin, Jeffrey N; Horberg, Michael A; Boyd, Cynthia M; Kitahata, Mari M; et al.
Abstract : The prevalence of multimorbidity increased nearly 3-fold from 2000 to 2009 among antiretroviral therapy–treated persons aging with human immunodeficiency virus, and it was higher among individuals who were older or white or reported a history of heterosexual contact. Hypertension and hypercholesterolemia were prominent conditions every year. Abstract: Background: Age-associated conditions are increasingly common among persons living with human immunodeficiency virus (HIV) (PLWH). A longitudinal investigation of their accrual is needed given their implications on clinical care complexity. We examined trends in the co-occurrence of age-associated conditions among PLWH receiving clinical care, and differences in their prevalence by demographic subgroup. Methods: This cohort study was nested within the North American AIDS Cohort Collaboration on Research and Design. Participants from HIV outpatient clinics were antiretroviral therapy–exposed PLWH receiving clinical care (ie, ≥1 CD4 count) in the United States during 2000–2009. Multimorbidity was irreversible, defined as having ≥2: hypertension, diabetes mellitus, chronic kidney disease, hypercholesterolemia, end-stage liver disease, or non–AIDS-related cancer. Adjusted prevalence ratios (aPR) and 95% confidence intervals (CIs) comparing demographic subgroups were obtained by Poisson regression with robust error variance, using generalized estimating equations for repeated measures. Results: Among 22969 adults, 79% were male, 36% were black, and the median baseline age was 40 years (interquartile range, 34–46 years). Between 2000 and 2009, multimorbidity prevalence increased from 8.2% to 22.4% ( P trend < .001). Adjusting for age, this trend was still significant ( P < .001). There was no difference by sex, but blacks were less likely than whites to have multimorbidity (aPR, 0.87; 95% CI, .77–.99). Multimorbidity was the highest among heterosexuals, relative to men who have sex with men (aPR, 1.16; 95% CI, 1.01–1.34). Hypertension and hypercholesterolemia most commonly co-occurred. Conclusions: Multimorbidity prevalence has increased among PLWH. Comorbidity prevention and multisubspecialty management of increasingly complex healthcare needs will be vital to ensuring that they receive needed care.